The interconnection of ideological paradigms in the history of Ukrainian culture - Volodymyr Fed (Cхід, 2013)
The article is devoted to theoretical consideration of interconnections of the mythological, religious and scientific paradigms in the origins of Ukrainian spirituality. Author came to conclusion that the paradigms interacted on the basis of complementarity of the philosophical foundation, conditions of which were dictated by historical time.